Becoming a "True Blues Fan": Blues tourism and performances of the King Biscuit Blues Festival. (April 2014) - Fry, Robert W
Helena, Arkansas' King Biscuit Blues Festival is a mass-produced event, where detailed schedules outline musical performances and regulate most aspects of the festival experience, yet many blues fans perceive their festival attendance as a homecoming. Such a perception is largely thanks to festival organizers and local merchants, who provide fans with an illusion of locality through performances of intimacy within the theatrical spaces of Helena's backstage areas. In this article, I illustrate the importance of a perceived and performed locality in the realization of both the fan experience and the annual festival. Through such inclusive experiences, fans move beyond the role of spectator and, in their assumption of true fandom, encounter a heightened blues experience, take on the role of the local culture, and become a vital part of Helena's multifaceted blues tradition. Through such fan performances, Helena and its blues tradition are revived, ensuring the success of the festival, the survival of its host city, and a continued theatrical space for performances of individuality, community, tradition, and "true" fandom.